The Achille’s heel of Prof. Friedman’s counter-revolution - GAMBINO, A. (PSL Quarterly Review, 2014)
The article considers Milton Friedman’s counter revolution in monetary theory. In effect, this counter-revolution starts with a reaffirmation, supported by an up-to-date re-elaboration, of the ultra secular quantity theory as far as this theory gives outstanding prominence to the changes in the quantity of money as being decisive elements in the changes of prices and income levels. The author argues, however, that while the condition concerning the parallelism between the growths of real income and those of the quantity of money certainly represents a necessary condition, it is not the one that is sufficient for price stabilisation. For this purpose, account must also be taken of the “fundamental equations” given by Keynes in his Treatise on Money, in order to establish the necessity of the equilibrium, in the sense of adjustment, between savings and investments. Accordingly, Friedman’s neglect to take these conditions into account constitutes the “Achilles’ heel” of the counter-revolution. JEL: B31, B22, E40, E50